2020
DOI: 10.1001/jamaoncol.2019.6650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pembrolizumab Plus Neoadjuvant Chemotherapy on Pathologic Complete Response in Women With Early-Stage Breast Cancer

Abstract: IMPORTANCEApproximately 25% of patients with early-stage breast cancer who receive (neo)adjuvant chemotherapy experience a recurrence within 5 years. Improvements in therapy are greatly needed.OBJECTIVE To determine if pembrolizumab plus neoadjuvant chemotherapy (NACT) in early-stage breast cancer is likely to be successful in a 300-patient, confirmatory randomized phase 3 neoadjuvant clinical trial. DESIGN, SETTING, AND PARTICIPANTSThe I-SPY2 study is an ongoing open-label, multicenter, adaptively randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
410
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 527 publications
(467 citation statements)
references
References 27 publications
4
410
0
1
Order By: Relevance
“…The combination of ICIs with chemotherapy in earlystage TNBC has also demonstrated preliminary success (Table 3). Among patients with stage II-III disease, the I-SPY 2 trial (ClinicalTrials.gov identifier: NCT01042379) initially revealed that pembrolizumab added to neoadjuvant paclitaxel followed by doxorubicin and cyclophosphamide nearly tripled the estimated pathologic complete response (pCR) rates from 22% to 60%, 31 perhaps related to the known immunostimulatory effects of anthracyclines to increase intratumoral immune effectors, 32 as well as antigen uptake and processing. 33 However, the GeparNuevo trial (NCT02685059), which included earlier-stage T1b and higher disease, demonstrated that the addition of durvalumab to neoadjuvant nab-paclitaxel followed by epirubicin and cyclophosphamide did not significantly improve pCR rates in the overall trial and only improved pCR rates when durvalumab was started 2 weeks before chemotherapy, which was a subgroup analysis underpowered for significance testing.…”
Section: Early-stage Chemotherapy Combination Regimensmentioning
confidence: 99%
“…The combination of ICIs with chemotherapy in earlystage TNBC has also demonstrated preliminary success (Table 3). Among patients with stage II-III disease, the I-SPY 2 trial (ClinicalTrials.gov identifier: NCT01042379) initially revealed that pembrolizumab added to neoadjuvant paclitaxel followed by doxorubicin and cyclophosphamide nearly tripled the estimated pathologic complete response (pCR) rates from 22% to 60%, 31 perhaps related to the known immunostimulatory effects of anthracyclines to increase intratumoral immune effectors, 32 as well as antigen uptake and processing. 33 However, the GeparNuevo trial (NCT02685059), which included earlier-stage T1b and higher disease, demonstrated that the addition of durvalumab to neoadjuvant nab-paclitaxel followed by epirubicin and cyclophosphamide did not significantly improve pCR rates in the overall trial and only improved pCR rates when durvalumab was started 2 weeks before chemotherapy, which was a subgroup analysis underpowered for significance testing.…”
Section: Early-stage Chemotherapy Combination Regimensmentioning
confidence: 99%
“…Based on this study, atezolizumab has been approved by the FDA and EMA in combination with taxanes for metastatic TNBC. Further, in early studies of preoperative therapy, the combination of PD-1 blockade and chemotherapy has produced a substantial increase in response rates, compared to chemotherapy alone, for both ER+/HER-2 negative and triple negative BC patients [9,10]. Our study rationale is in line with these ndings, combining checkpoint blockade with a carefully selected chemotherapy regimen, as 1 st / 2 nd line metastatic treatment.…”
Section: Introductionmentioning
confidence: 68%
“…Immunotherapy with PD-1 and CTLA-4 inhibitors has shown remarkable clinical e cacy against several cancer forms [1][2][3][4][5][6] and now show activity in breast cancer [7][8][9][10]. This includes durable responses in metastatic breast cancer (mBC) patients, amid minimal adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…The I-SPY 2 phase II trial evaluated the addition of pembrolizumab to standard NACT, showing a 40% improvement in the probability of pCR compared to the control arm (60% vs. 22%) [97]. Furthermore, in the phase Ib Keynote-173 trial, a multicohort study assessing the safety and the efficacy of pembrolizumab combined with various schedules and doses of platinum and taxanes followed by AC as NACT, the pCR rate across all cohorts ranged from 60% to 80%, with the best response registered in the subgroup of patients treated with pembrolizumab added to nab-paclitaxel plus carboplatin [98].…”
Section: Immunotherapy For Early Tnbcmentioning
confidence: 99%